Improving Local Government Performance Through Tax Optimization - Riyanto Wujarso; Saprudin Saprudin; Anton Zulkarnain Sianipar; Revan Andhitiyara; Arie Martin Parulian Napitupulu (Universitas Sultan Ageng Tirtayasa, 2022)
Abstract: Taxes play an important role in the functioning of the state, particularly in the implementation of development initiatives. Similar to taxes levied against the federal government, regional taxes play an important role in the performance of state and local government functions. Regional taxes are used for a variety of purposes, including regulation, budgeting, redistribution, resource allocation, and a combination of these. To be considered excellent, a local tax must, in principle, be able to enhance local revenue, which in turn improves the functioning of local government. As a result, initiatives to improve the functioning of local governments through the optimization of local tax collections are discussed in this paper. The descriptive qualitative method is being used in this investigation. It was discovered from the study's findings that a source of funding, which is primarily derived from local revenue (also known as PAD), is required for the implementation of autonomy and decentralization. Local taxes and levies should be used to fund PAD, but the contribution is currently small, accounting for only 16 percent of total PAD. Increased regional income can be achieved by maximizing the intensification of local tax collections and regional levies, which can be done in the case of attempts to improve regional performance, as previously stated.Keywords: Local Tax, Local Government, Performance, Local Revenue (PAD).